Harmonizing the Interests of Free Speech, Obscenity, and Child Pornography in Cyberspace: The New Roles of Parents, Technology, and Legislation for Internet Safety - Amos O. Olagunju (The Scientific World Journal)
Inadvertent access to website addresses and spam e-mails continue to make pornography rampant on the Internet in schools, homes, and libraries. Collectively, parents, teachers, and members of the community must become more aware of the risks and consequences of open access to the Internet, and the distinction between censorship and Internet access filtering. Parental involvement is crucial for raising children with healthy Internet habits to access social and educational materials. Although generations have coped with different times and trials, technology is ushering in new trials. Parents and communities cannot ignore the present and future technology ingrained into the lives of children. This paper contends that parents armed with legislation and technological security devices for access to the Internet ought to strengthen the character of online Internet safety. The discussion is focused on the roles that parents, communities, technology, and laws should play in order to protect children from obscene and pornographic threats from cyberspace. It is argued that the roles of education and technology should outweigh the legislative interventions of governments. A critique of significant litigations and laws on obscenity and pornography is presented. The paper offers a variety of security tools and techniques for protecting children from Internet access to obscene and pornographic materials. The impacts of pornographic materials on the welfare of children, adolescents, women, and families are discussed.